2016
DOI: 10.1002/admi.201601029
|View full text |Cite
|
Sign up to set email alerts
|

Double Nanoporous Structure with Nanoporous PtFe Embedded in Graphene Nanopores: Highly Efficient Bifunctional Electrocatalysts for Hydrogen Evolution and Oxygen Reduction

Abstract: Pt‐based alloys are considered the universal choice among electrocatalysts for both hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). However, improving the electrocatalytic efficiency with the use of minimal amount of Pt is very challenging. A new strategy has been developed to fabricate a “double nanoporous” structure, in which nanoporous PtFe alloy (np‐PtFe) is embedded in nanoporous graphene (NPG), through in situ etching and acid leaching treatments. The np‐PtFe/NPG‐700 served as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…The spectrum of Pt5Ni10-dewetted (thermal treatment in H 2 /Ar) shows the typical signature of Pt metal: [41] that is, two sharp peaks at % 75.1 and 71.7 eV associated to the Pt 4f 5/2 and Pt 4f 7/2 signals, respectively. [52] This confirms the metallic state of Pt (Pt 0 ) in particles dewetted from both Pt films or Pt-Ni bilayers. Moreover, the Pt 4f peaks of Pt5Ni10dealloyed show a minor shift towards higher B.E.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The spectrum of Pt5Ni10-dewetted (thermal treatment in H 2 /Ar) shows the typical signature of Pt metal: [41] that is, two sharp peaks at % 75.1 and 71.7 eV associated to the Pt 4f 5/2 and Pt 4f 7/2 signals, respectively. [52] This confirms the metallic state of Pt (Pt 0 ) in particles dewetted from both Pt films or Pt-Ni bilayers. Moreover, the Pt 4f peaks of Pt5Ni10dealloyed show a minor shift towards higher B.E.…”
Section: Resultssupporting
confidence: 65%
“…On the contrary, both spectra of samples Pt5Ni10‐dewetted and Pt5Ni10‐dealloyed only slightly differ from the reference (Pt5‐dewetted). The spectrum of Pt5Ni10‐dewetted (thermal treatment in H 2 /Ar) shows the typical signature of Pt metal: that is, two sharp peaks at ≈75.1 and 71.7 eV associated to the Pt 4f 5/2 and Pt 4f 7/2 signals, respectively . This confirms the metallic state of Pt (Pt 0 ) in particles dewetted from both Pt films or Pt‐Ni bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the OERk ineticso fe lectrocatalysts are elucidated by the Tafel plots, which are converted by the Ta fel equation (h = a + b log j j j ;w here h is the overpotential, b is the Ta fel slope, and j is the current density) in Figure4b. [33] The smaller the Ta fel slope, the greater the change in the OER rate with an increase of overpotential. [34] The Am-CFDH/NCNTs hybrid owns the lowestT afel slope of 56.88 mV dec À1 among that of Am-CFDH/CNTs( 80.35 mV dec À1 ), Am-CFDH (64.90 mV dec À1 ), NCNTs( 153.65 mV dec À1 ), and CNTs (260.77 mV dec À1 ), indicating that the target catalyst has satisfactory OERk inetics.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the OER kinetics of electrocatalysts are elucidated by the Tafel plots, which are converted by the Tafel equation ( η = a + b log | j |; where η is the overpotential, b is the Tafel slope, and j is the current density) in Figure b . The smaller the Tafel slope, the greater the change in the OER rate with an increase of overpotential .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, downsizing Pt to singleatom scale can maximize the atom utilization by exposing nearly all the metal atoms as active sites, which will be discussed later (vide infra). Alloying Pt-group metals with other non-noble metals (such as Cu [17,18], Fe [19], Co [20,21]) can also be used to lower the loading. Previous studies have suggested that metal Ni possesses a moderate hydrogen binding energy close to that of Pt, and Pt-Ni alloy may thus exhibit profitable electronic and synergistic effect for HER.…”
Section: At 4 Ma CMmentioning
confidence: 99%